Penerapan Metode Multi Objective Optimazion on The Basic Of Ratio Analysis (MOORA) pada Pengambilan Keputusan Penentuan Jurusan bagi Siswa Kelas X Reguler di SMA Negeri 1 Cawas - Fera Tri Wulandari; Noviana Noviana; Aryati Wuryandari (Universitas Boyolali, 2023)
Senior High School (SMA) is a secondary education level in formal education in which there are majors so that students are more focused on one form of learning group according to their interests and potential. SMA Negeri 1 Cawas often experiences time constraints in carrying out the student majoring process, this is caused by a lack of facilities that can help schools to simplify and speed up the student majoring process so that reports that should have been made are still being processed. The decision support system was created to facilitate the determination of major classes and speed up the process of dividing majors. Data processing in this study uses the MOORA method. This system processes student data, criteria data, value data, and department data. With this system, it can be used as an alternative to help schools to make it easier in the process of determining and classifying major classes and speeding up the process of dividing student majors.